Attitudes towards mental health and seeking mental health services: A perspective of Arabs living in the UK - Sultan, Arwa (2020)
This study examined whether or not ethnicity was predictive of attitudes towards seeking mental health services. Participants completed an online questionnaire advertised on social media outlets. Results showed that Arabs showed significantly more shame-focused attitudes towards mental health when compared with their White British counterparts (N = 50). Ethnicity was not found to be a predictive factor for attitudes towards seeking mental health services. However, stigma and shame-focused attitudes towards mental health were predictive of less favorable attitudes to seeking mental health services. Implications are drawn from the results.